Temporal lobe rating scale: application to Alzheimer's disease and frontotemporal dementia. Issue 2 (1st February 2001) - Galton, C J; Gomez-Anson, B; Antoun, N; Scheltens, P; Patterson, K; Graves, M; Sahakian, B J; Hodges, J R
Abstract : OBJECTIVES: Temporal lobe atrophy as assessed by MRI can be measured in several ways. Volumetric measurements are quantitative but very time consuming and require extensive training to perform, so are not easily transferable to clinical practice. Visual rating scales, by contrast, are quick and widely applicable. Although medial temporal lobe atrophy is well described in Alzheimer's disease (AD), it is uncertain how early these changes can be detected and whether they discriminate AD from other neurodegenerative diseases, most notably frontotemporal dementia (FTD). The objectives were (1) to develop a widely applicable temporal lobe rating scale, and (2) to characterise and quantify the patterns of temporal lobe atrophy in AD versus temporal and frontal variants of FTD. METHODS: The temporal lobe assessments were made using an established hippocampal rating scale extended to incorporate additional temporal regions. This was firstly validated with volumetric analysis and then applied to 30 probable AD, 30 FTD (consisting of 17 temporal variant (semantic dementia) and 13 frontal variant) and 18 control coronal MRI images. RESULTS: Bilateral hippocampal atrophy was found in 50% of the patients with AD. Contrary to expectations, patients with semantic dementia also had hippocampal atrophy, which for the left side exceeded that seen in AD; other regions (temporal pole, parahippocampal gyrus, and lateral temporal lobe), spared in AD, were severely atrophied in this group. The patients with frontal variant FTD occupied an intermediate position and were largely indistinguishable from AD. CONCLUSIONS: Hippocampal atrophy is, therefore, not specific for AD. Semantic dementia can be distinguished from AD, by the presence of severe bilateral atrophy of the temporal pole, parahippocampal and lateral regions. These findings have implications for the differential diagnosis of dementias.